Different Names for the Same Thing...? Nielsen’s Forces, Schenker’s Striving, Tarasti’s Modalities and Simpson’s Narratives - Pankhurst, Tom (Carl Nielsen Studies, 2003)
Carl Nielsen said that titles for his third and fourth symphonies were ‘actually just different names for the same thing, the only thing that music in the end can express: resting forces as opposed to active ones’ (cited in Fanning (1997) 97). This article attempts to describe the articulation of these forces in The Inextinguishable in terms of A. J. Greimas’s model of narrative. It concentrates first on some details regarding the second subject before considering how Nielsen pushes at the boundaries of tonality at various points in the work.